Coverage and access of plant clinic in Nepal - Adhikari, D.; Sharma, D.R.; Pandit, V.; Schaffner, U.; Jenner, W.; Dougoud, J. (Journal of Agriculture and Environment, 2018)
Plant clinic is one of the extension approaches that deliver field level services to farmers. In Nepal, this service started in 2008. An assessment of the coverage and access of Plantwise plant clinic in Nepal was conducted from 2013 to 2016 with the view to assess the performance of this approach. The number of plant clinic sessions and queries by farmers increased from 2013 to 2014 whereas in 2015 the numbers of both sessions and queries decreased due to the earthquake that struck the country in April 2015 and disturbances throughout the year. The average number of clinic session run per year was 10.5 and the average number of queries per session was 12. The farmers’ gender ratio for female to male who visited the clinic was 45:55. The coverage and access of plant clinics is increasing, but plant clinics are not yet widespread across Nepal.